Coronavirus: In Timbuktu youth is at the forefront of raising awareness against COVID-19 - Mohamed Mahmoud Elhadj (Freedom from Fear, 2020)
In its efforts to raise awareness against the coronavirus, the association “The voice of the students of Timbuktu” has just trained around thirty young people in respect of measures to stop the contagion. The training can be recognized as a means to strengthen the prevention of COVID-19 in Timbuktu, where nothing seems to worry the population.